SYSTEMATIC LITERATUR REVIEW: EQUITY CROWDFUNDING DALAM PERSPEKTIF INVESTOR - Sumayyah, Sumayyah; Zahara, Inna (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
Systematic literature review, Equity Crowdfunding,Fintech, Perlindungan Investor, UMKM. Abstract− The equity crowdfunding business is also based on the principle of trust between the party providing funds, namely investors, and the party managing the funds of MSME actors. So from the case above, it seems that security and protection for investors is not directly proportional to the opportunities for business actors to obtain alternative capital. Therefore, equity crowdfunding investment can also be linked to agency theory. In this research, the descriptive qualitative method is proxied by a literature review. OJK regulations already contain consumer complaint services in the financial services sector. This regulation covers Equity Crowdfunding as a business subject and financial services institution. However, this regulation only provides facilities for consumers who have experienced losses due to violations by business subjects, so the existing protection approach is repressive. Meanwhile, in the context of implementing equity crowdfunding, which is included in the capital markets sector, the legal protection approach that is more emphasized is preventive protection. This is due to the importance of investor confidence in placing their investments in the capital market.